Japanese and Taiwanese University Students’ Summaries: A Comparison of Perceptions of Summary Writing - Ono, Masumi (Journal of Academic Writing, 2011)
The study investigated Japanese and Taiwanese postgraduate students’ perceptions of summary writing. Eight Japanese and eight Taiwanese students who speak English as a Foreign Language (EFL) at a university in England participated in the summary writing task in English, questionnaires, and follow-up interviews. The questionnaire and interview data were analysed in terms of (a) students’ background knowledge on summarising and (b) educational background regarding experiences of summarisation and summary writing instruction taught in classes. The results revealed that the Japanese and Taiwanese students shared similar opinions on definitions of summary writing. The students in both groups tended to be self-taught in L1 summarisation due to little L1 summary writing instruction. ESL/EFL writing teachers should note that students from different countries may have culture-specific summary writing conventions and that students from the same country may have different summarisation experiences and perceptions of textual features.